(untitled) (Ticontre. Theory Text Translation, 2022)
The essay proposes an overall evaluation of the historiographic approach underlying the eighteenth-century studies of Giulio Natali (1875-1965), an approach to which various labels have been attributed over time (late positivism, anti-Chianism, a mixture of historicism and aesthetic criticism) although none of these correctly identifies the authentic cultural profile of the critic.